Response to Comment on: A simplified frailty score predicts outcome in curatively treated older patients with classical Hodgkin lymphoma - Kjersti Lia; Rasmus Rask Kragh Jørgensen; Per Wikman; Bente L. Wold; Ninja Övergaard; Øystein Fluge; Unn-Merete Fagerli; Hanne Bersvendsen; Idun B. Bø; Sameer Bhargava; Daniel Molin; Alexander Fosså (Haematologica)
Not available.